1971
DOI: 10.1172/jci106641
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response relationship of luteinizing hormone to luteinizing hormone—releasing hormone in man

Abstract: A B S T R A C T In previous clinical studies with highly purified porcine luteinizing hormone-releasing hormone (LH-RH), administration of the somewhat arbitrarily chosen doses of 700-1500 jg resulted in increased serum levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…It has been reported that a highly purified LH-RH caused a significant increase in plasma LH and FSH values (Kastin et al, 1969) and the present study employed synthetic LH-RH again demonstrated that LH-RH released FSH as well as LH, even though the response of FSH was less as compared with that of LH, supporting a view that LH-RH has an intrinsic activity of FSH-RH (Schally et al, 1917a(Schally et al, , 1971bKastin et al, 1971).…”
supporting
confidence: 80%
“…It has been reported that a highly purified LH-RH caused a significant increase in plasma LH and FSH values (Kastin et al, 1969) and the present study employed synthetic LH-RH again demonstrated that LH-RH released FSH as well as LH, even though the response of FSH was less as compared with that of LH, supporting a view that LH-RH has an intrinsic activity of FSH-RH (Schally et al, 1917a(Schally et al, , 1971bKastin et al, 1971).…”
supporting
confidence: 80%
“…Previous studies have shown that adult men and women respond to the administration of highly purified porcine LH-RH with a significant release of LH [5][6][7]. No significant difference in response between men and women was found [5].…”
Section: Discussionmentioning
confidence: 88%
“…Administration of porcine LH-RH clearly was shown to increase levels in serum of LH and follicle-stimulating hormone (FSH) in normal men and women [5], even when injected subcutaneously [6]. A linear log dose-response relation has been demonstrated with this material [7]. The increased release of gonadotropins occurred regardless of whether the initial levels of LH and FSH were elevated, as in postmenopausal women [6] and in men [8] pretreated with clomiphene, or whether LH was suppressed by estrogen or an oral contraceptive [5,6].…”
Section: Introductionmentioning
confidence: 81%
“…These early studies uniformly administered pharmacologic quantities of GnRH stimulation to men, women, and children within intact, endogenous GnRH secretion. In one study, individual doses of GnRH (up to 3,000 µg) were often administered weeks apart [1,2,3,4,5]. Despite these limitations of dose and frequency and the potential interference of endogenous GnRH secretion, significant linear dose-response relationships between the log of the GnRH dose and pituitary LH secretion were described when such pharmacologic doses were utilized [1,2,3, 6].…”
Section: Introductionmentioning
confidence: 99%